1991
DOI: 10.1073/pnas.88.17.7528
|View full text |Cite
|
Sign up to set email alerts
|

Deletional switch recombination occurs in interleukin-4-induced isotype switching to IgE expression by human B cells.

Abstract: There is controversy as to whether deletional rearrangement occurs between the IgM and IgE switch regions (S, and S,, respectively) during switching to the IgE isotype.We have addressed the issue by stimulating normal human B cells, sorted for lack of expression of surface IgE, to produce IgE by infection with Epstein-Barr virus (EBV) in the presence of interleukin 4 (IL-4). Genomic DNA was amplified for Sp/Se switch junction fragments by utilizing the nested-primer polymerase chain reaction. Switch junction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 34 publications
(16 reference statements)
0
38
0
2
Order By: Relevance
“…The regulation and existence of IgE memory B cells is controversial and poorly understood (50)(51)(52)(53)(54)(55)(56). It has been suggested that a significant fraction of IgE memory resides in the IgG1 compartment, with generation of a memory IgE response resulting from sequential switching of IgG1 memory B cells to the IgE B cell lineage (50,54,(57)(58)(59)(60)(61)(62)(63)(64). While our studies have not directly addressed this issue, it is interesting that we and others have observed that both primary and memory IgE responses occur prior to IgG1 responses in our immunization and asthma models, perhaps indicating that the vast majority of IgE responses do not develop by a sequential switching mechanism through an IgG1 B cell intermediate.…”
Section: Figurementioning
confidence: 99%
“…The regulation and existence of IgE memory B cells is controversial and poorly understood (50)(51)(52)(53)(54)(55)(56). It has been suggested that a significant fraction of IgE memory resides in the IgG1 compartment, with generation of a memory IgE response resulting from sequential switching of IgG1 memory B cells to the IgE B cell lineage (50,54,(57)(58)(59)(60)(61)(62)(63)(64). While our studies have not directly addressed this issue, it is interesting that we and others have observed that both primary and memory IgE responses occur prior to IgG1 responses in our immunization and asthma models, perhaps indicating that the vast majority of IgE responses do not develop by a sequential switching mechanism through an IgG1 B cell intermediate.…”
Section: Figurementioning
confidence: 99%
“…We have previously shown that nested primer PCR amplifies switch fragments from as little as 10 pg (one diploid genome) of DNA from the IgE plasmacytoma U266 (3). If all the B cells containing cytoplasmic IgE in the CD40/IL,4 system (=10% of the total B cells) had undergone deletional switch recombination, switch fragments should have been detected in 100 pg DNA samples.…”
Section: P P Smentioning
confidence: 99%
“…Highly purified human peripheral blood B cells from nonatopic subjects were isolated and cultured as previously described (1). slgE-B cells were obtained by cell sorting (3). Resting B cells were collected at the 50-60% interface after Percoll gradient centrifugation (4).…”
Section: B Cellmentioning
confidence: 99%
See 2 more Smart Citations